Semiotics Analysis on World Health Organization Instagram Post - Yanti , Luh Mita Wida; Suastini , Ni Wayan; Hikmaharyanti , Pt. Desi Anggerina (Institut Pariwisata dan Bisnis Internasional, 2023)
This study is aimed to analyze the type of signs and meaning found in pictures related to Covid-19 post by World Health Organization (WHO) in their Instagram account. This study used observation method to collected the data that taken from Instagram Post by World Health Organization, afterward, to analyzing the data this study applied the qualitative method. This study were analyzed using theory of Semiotics by Saussure (1959) in order to find out verbal signs and Barthes (1964) theory of Denotation and Connotation to explain the reality. The data were presenting by using formal and informal method. The data finding of this study showed there are 8 verbal signs in both of data. Those type of signs consist of Connotation and Denotation.